THE INTERIOR BALLISTICS MODEL OF THE GRENADE LAUNCHER SYSTEM WITH THE PHENOMENON OF PROPELLANT POWDER BURNING INCOMPLETELY IN HIGH-PRESSURE CHAMBER - Hoàn (Journal of Military Science and Technology, 2021)
The model of Interior ballistics with high-low pressure chambers is used popularly in the grenade launchers with the assumption: Propellant powder completely burning into gases. However, the reality is there’s a bit of Propellant powder burning incompletely in a high-pressure chamber and flow through one or more nozzles (orifices) in the low-pressure chamber and keep burning. Therefore, the above assumption will lead to calculation errors and must be corrected by matching coefficients. This article proposes a grenade launch system model, which includes the phenomenon of jet-outflow from a high-pressure chamber to a low-pressure chamber is a two-phase flow of gas and incomplete burning particles; these particles continue to burn in the low-pressure chamber. The purpose of the model is to improve the theoretical basis and diversify the approach when solving the Interior ballistics of grenade launchers. Calculation and testing for the system of DP-64 gun and FG-45 ammunition for the incomplete burning coefficient of the Propellant in the high-pressure chamber is 0,22.